Impact of Economic Growth and Quality of Human Resources on Unemployment: Central Sulawesi Case Study 2016-2020 - Paembonan, Laendatu; Yohan; Nabir, Rahmayanti (International Journal of Social Science and Business, 2024)
This study aims to determine the effect of economic growth and the quality of human resources on the open unemployment rate in Central Sulawesi Province. The use of panel data regression is essential to find the magnitude of the influence of economic growth variables and the quality of human resources on the open unemployment rate in Central Sulawesi Province to be used as a basis for analysis. The results showed that high economic growth and the increase in the Human Development Index (HDI) in Central Sulawesi Province have not reduced the open unemployment rate in Central Sulawesi Province. Based on the results of regression panel data, this condition shows that economic growth has a positive but insignificant effect on unemployment because the classification of mining and quarrying business fields still supports economic growth. The quality of human resources (H.R.) has a negative but not significant effect on the open unemployment rate in Central Sulawesi in the 2010-2020 period because the improvement in the quality of human resources has not been evenly distributed in areas in Central Sulawesi Province, especially in the regions that rely on mining and quarrying activities that receive more workers from outside Central Sulawesi Province. This research still needs to be continued by considering the variables of wages and working hours in the research model.